Contending conceptions of ownership in urbanizing China - Pils, Eva (Cambridge University Press, 2010)
Among the incidents drawing attention to the problem discussed here, the self-immolation of a woman named Tang Fuzhen in December 2009 was one of the most widely discussed. Facing the forced demolition of her home, she stood on the roof of the building, doused herself in petrol and, after vainly urging the demolition team to stop beating members of her family, set herself on fire. Her suicide (she succumbed to her injuries a few days later) was captured on camera, and the video clip showing her, a dark, then suddenly aflame, silhouette against the sky, amongst the shouts of shocked observers in the street below, was widely circulated on the internet. As urbanisation has progressed rapidly, the effects of urban development – to be precise, of urban redevelopment and of the expansion of cities into the countryside – on citizens affected by demolition and expropriation of land or houses has been great in China. While they have no real choice in the face of an order to ‘develop’ or redevelop their area through urban construction, not all residents actually oppose such measures. Some are glad to accept compensation payments, which can be substantial and that have given rise to the term ‘demolition nabob’. But invariably, some residents are opposed to their removal, and become involved in fights with the government that may cost them far more than just their residences. The experiences of these activist evictees have drawn much public attention, and are among the reasons for continued criticism of the existing regime of ownership and use rights in immoveable property (land and buildings).
CRIS-Team Scopus Importer:2024-06-26